Two-channel electric liquid helium level meter - K. K. Kim; A. A. Tkachuk; A. A. Kuznetsov (Омский научный вестник)
The liquid helium level meter for the transport cryomodules of high-speed ground vehicles with the magnetic suspension is presented in the article. The need to develop such a meter is dictated by the specifics of the functioning of cryomodules that are part of transport systems, namely, functioning in the strong magnetic fields. We consider the operation principle of the measuring system of this meter. We draw conclusions about the accuracy of its measurements. The possibility of using the multichannel sensor system with the sensors and the switching device in the secondary device circuit has been determined.